(untitled) (Research, Society and Development, 2023)
Alzheimer’s disease (AD) is one of the most common neurodegenerative disorders in the world and has been listed as a global public health priority by the WHO. There is currently no effective treatment for the disease and its cause is still unknown. In recent years, attempts have been made to explain the etiological mechanisms of AD, one proposed hypothesis is the spread of oral microorganisms such as Porphyromonas gingivalis (Pg) to brain tissue in patients with periodontitis. However, this possible causal relationship remains unclear. Objective: to present the role of Pg as a link between periodontitis and Alzheimer’s disease based on a literature review of publications from the last 5 years. Materials and methods: search of publications in the following databases: PubMed, SpringerLink, Scientific Direct, Scielo. Results: 19 scientific articles were included of which animal and molecular studies determine that, Pg infection increased the production of inflammatory mediators, thus causing an increase in the production of Aβ (beta amyloid) and subsequently, neurodegeneration compatible with AD; however, no clear relationship has been established in human studies. Conclusion: the effect of Pg on the development of neuroinflammation has been demonstrated; however, further large-scale studies and longitudinal follow-up in humans are needed to better establish the relationship between periodontitis and AD.